SUN-LB1 Atypical Presentation Of Myocardial Infarction In A Young Patient With Polycystic Ovarian Syndrome - Mandal, Shobha (J Endocr Soc, 2020)
Background: Polycystic ovarian syndrome (PCOS) is a very common and complex endocrine problem in women of childbearing age, with a prevalence of 4 to 12% globally. Myocardial infarction (MI) is the leading cause of death in women worldwide. PCOS increases the risk of MI because of chronic inflammation, endothelial dysfunction, impaired pulse wave velocity and its association with metabolic syndrome, and hormonal imbalance. Clinical Case: A 36-year-old female with a history of PCOS, hirsutism, severe acne on spironolactone, presented to ER with a chief complaint of lower back pain for 10 days that started after lifting a 60-pounds printer. The pain was attributed to musculoskeletal type, one dose of ketorolac intramuscularly was given and she was discharged on cyclobenzaprine. The next morning, she presented with worsening back pain and new-onset vomiting. Physical exam was normal except for BMI 34.6kg/m2; vitals were stable. Lab work showed elevated troponin of 1.43 which rose to 10.6 ng/ml (normal 0.00-0.034), cholesterol 125 mg/dL (less than 200), HDL 33 mg/dL (normal 40-59), LDL 164 mg/dL (normal 100-129). Electrocardiogram showed sinus tachycardia with Q wave changes in leads III and V1 to V3. Echocardiogram showed hypokinesia of left ventricular wall in the mid to apical anterior septum. Computed tomography (CT) scan of the thoracic spine was negative for abscess or fracture. CT of abdomen and pelvis as well as CT angiography chest were negative. Urine drug screening was also negative. As her presentation was attributed to MI, patient was started on heparin drip, aspirin, atorvastatin, and metoprolol. She underwent cardiac catheterization that showed 99% ostial left anterior descending artery stenosis; a drug-eluting stent was successfully placed. After intervention her back pain resolved. She was discharged on dual antiplatelet therapy (aspirin and Prasugrel) along with atorvastatin, metoprolol and nitroglycerin. Conclusion: This case suggests an association of PCOS with MI. A meta-analysis has shown a two-fold increase in risk of coronary artery disease in patients with PCOS (1). Future studies are need to examine opportunities for cardiovascular disease risk reduction in PCOS patients. Reference:1. de Groot PCM, Dekkers OM, Romijn JA, Dieben SWM, Helmerhorst FM. PCOS, coronary heart disease, stroke and the influence of obesity: a systematic review and meta-analysis. Human Reproduction Update 2011. 17 495-500.